2011
DOI: 10.1089/end.2010.0439
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Tamsulosin After Shock Wave Lithotripsy in the Treatment of Renal and Ureteral Calculi?

Abstract: At last, this study suggested that tamsulosin facilitate earlier clearance of fragments after ESWL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 20 publications
0
14
2
1
Order By: Relevance
“…Contrary to our findings, most of the investigators [12,25,26] have shown that tamsulosin facilitates earlier clearance of stone fragments. We have no proper explanation for this finding.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to our findings, most of the investigators [12,25,26] have shown that tamsulosin facilitates earlier clearance of stone fragments. We have no proper explanation for this finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Gravina et al [15] in 2005, Losek and Mauro [14] in 2008, and Hossain et al [13] in 2011 found that renal SWL with adjunctive tamsulosin enhances the SFR. On the other hand, Micali et al [22] in 2007, Gravas et al [23] in 2007, Wang et al [24] in 2009, Falahatkar et al [12] in 2011, Zaytoun et al [25] in 2012 did not find any benefits of tamsulosin in increasing the SFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized controlled trial published in 2010 including 166 patients after SWL of renal calculi showed signifi cantly improved stone free rates at 3 months after using tamsulosin and diclofenac compared to diclofenac alone (73 % versus 55 %) [ 13 ]. Another randomized controlled trial found a signifi cant decrease in the time to stone passage in the group treated with tamsulosin compared to the placebo group [ 14 ]. A systematic review on MET after SWL by Schuler and coworkers [ 15 ] also showed a signifi cant increase in successful outcomes [ 15 ].…”
Section: Adjunctive Medical Treatmentmentioning
confidence: 99%
“…Embora não se tenha encontrado diferença estatística em relação a taxa de pacientes livres de cálculos (71,4% com alfa-bloqueador versus 60,6% com placebo; p=0,116), o grupo em uso de tamsulosina eliminou mais precocemente os fragmentos de cálculos (p=0,002) [78] . Em um outro estudo randomizado com 150 doentes avaliando os resultados da tamsulosina e da doxazosina após LECO, também não se encontrou vantagens na taxa de doentes livres de cálculos (84% placebo, 92% tamsulosina, 90% doxazosina), porém pacientes em uso de tamsulosina tiveram um significativo menor tempo para expulsão dos cálculos tanto em relação à doxazosina (p=0,026) como em relação ao placebo (p=0,002), e uma menor incidência de episódios de cólicas em relação aos outros dois grupos [79] .…”
Section: Terapia Expulsiva Medicamentosaunclassified